Assessing the Connection between Iron Deficiency with Severity of Chronic Heart Failure (Journal of Invasive and Clinical Cardiology, 2025)
Background: Based on epidemiologically research conducted in various countries, it has been found that iron deficiency is prevalent among individuals suffering from heart failure.Objective:  The purpose of present  study aimed to evaluate the association between Iron deficiency (ID) & severity of chronic Heart Failure(HF) in a tertiary care hospital of Bangladesh.Methods : This analytical cross sectional study conducted at the department of cardiology ,Sir Salimullah Medical College & Mitford hospital for six (6) months-1st July 2021 to 31st December 2021. A total of 96 patients with chronic HF were included & iron profile was evaluated in all the study patients. Severity will be assessed by LVEF(left ventricular ejection fraction)  & NYHA(New York heart Association) class.Result : A total of 96 patients were studied with 52.1%were male & 47.9% were female. Mean age of the patients was 58.5±12.3 (SD).years & where the majority were aged 61-70 years. About 54.2 % of patients had ID where 47.9% had absolute ID and 6.3% had functional ID according to the laboratory investigations. Presence of ID was significantly associated with NYHA HF class III & class IV & moderate and severe LV dysfunction (p